Behavioral Change and Family Disruption among Labor Migrants in Nepal - Pokharel, Ram Raj (Management Dynamics, 2020)
Sociological studies of migration are diverse. The motive for international labor migration includes political, economic, social, and environmental cause. In this regard, this study aims to explore the behavioral change among the labor migrants and the status of family disruption of the Nepalese involved in foreign labor migration. The study has been based on primary source, data collected from interview schedule by fulfilling the validity from the review of literature with the sample from Tribhuvan International Airport, and migrant returnee’s temporary residences such as hotels and guest house on accidental basis. The sample includes 102 respondents. The study concludes that the there is a behavioral change among the family members of the migrant labors. The study further concludes there has not been the family disruption among the family members of the migrant labors.